2020
DOI: 10.1002/ecs2.3199
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire severity and postfire salvage harvest effects on long‐term forest regeneration

Abstract: Following a wildfire, regeneration to forest can take decades to centuries and is no longer assured in many western U.S. environments given escalating wildfire severity and warming trends. After large fire years, managers prioritize where to allocate scarce planting resources, often with limited information on the factors that drive successful forest establishment. Where occurring, long‐term effects of postfire salvage operations can increase uncertainty of establishment. Here, we collected field data on postf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“…Because fire rarely consumes the boles of live trees, this pulse of delayed mortality can increase post-fire fuel levels by inputting additional biomass to snag and deadwood (down woody debris) pools (Fulé et al 2004;Stephens 2004;Hyde et al 2012, Stenzel et al 2019. Efforts to reduce these fuels through silvicultural treatment (i.e., salvage logging) have had mixed results, sometimes increasing fuel loads over the short term (i.e., Donato et al 2006, Johnson et al 2020a and sometimes reducing subsequent fire severity (i.e., Povak et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Because fire rarely consumes the boles of live trees, this pulse of delayed mortality can increase post-fire fuel levels by inputting additional biomass to snag and deadwood (down woody debris) pools (Fulé et al 2004;Stephens 2004;Hyde et al 2012, Stenzel et al 2019. Efforts to reduce these fuels through silvicultural treatment (i.e., salvage logging) have had mixed results, sometimes increasing fuel loads over the short term (i.e., Donato et al 2006, Johnson et al 2020a and sometimes reducing subsequent fire severity (i.e., Povak et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To assess the likelihood for post-fire recovery to forest (i.e., resilience), we compared post-fire stem densities to local silvicultural stocking recommendations and pre-fire stem densities. On lands managed by the USDA Forest Service in the Blue Mountains, minimum stocking recommendations range from ~60 trees ha −1 in lower elevation and drier forest types to >350 trees ha −1 in higher elevation and cooler-moister forest types (Powell 1999), and these stocking rates were used in similar post-fire regeneration studies of dry to moist mixed conifer forest types in the PNW (Povak et al 2020;Boag et al 2020). Specifically, we compared postfire stem density (sum of juveniles and surviving trees) for each plot to four post-fire stem density thresholds:…”
Section: Comparing Post-fire Stem Densities To Silvicultural Stocking...mentioning
confidence: 99%
“…The spatial configuration of fire-killed trees creates variability in distance to and quantity of available seeds (Turner 2010), and annual seed delivery varies with the infrequent production of large seed crops (Kelly 1994). When seeds are available, survival and growth of seedlings are modified by the topographic effects on soil moisture (Donato et al 2016;Hoecker et al 2020;Stewart et al 2021), competition from understory vegetation (Povak et al 2020;Owen et al 2020), species traits (Harvey et al 2016;Rodman et al 2020;Hoecker and Turner 2022), soil substrates (Burns and Honkala 1990), and subsequent disturbance (Turner et al 2019;Busby et al 2020). Most researchers have focused on the factors affecting the spatial variability in post-fire seedling density (as reviewed by Stevens-Rumann and Morgan 2019), whereas few researchers have examined factors affecting height growth, a critical factor for forecasting the future forest canopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of snags may reduce fire risk but also reduce or eliminate ecosystem function (Janisch and Harmon 2002;Lutz and Halpern 2006;Thorn et al 2020). Previous work in other forest types has shown that the results of salvage logging can sometimes increase fuel loads (i.e., Donato et al 2006) and sometimes reduce subsequent fire risk (i.e., Povak et al 2020).…”
Section: Introductionmentioning
confidence: 99%